Pengaruh Kualitas Website, Flash Sale, Dan Dorongan Berbelanja Terhadap Pembelian Impulsif Produk Fashion Di Shopee Mmelalui Emosi Positif - Ade Jesica; Farida Indriani (Jurnal Akuntansi dan Pajak, 2023)
This research aims to analyze the influence of website quality, sales promotion, hedonic shopping motives towards the purchase impulsive of Shopee through positive emotion as the intervening variable. The sampling method used on this research is non-probability sampling with purposive sampling technique. Samples were collected from 100 respondents on Pekanbaru who knows the information about Shopee and purchase fashion products at shopee. Analysis method used here is multiple regression analysis which includes validity test, reliability test, classic assumption test, multiple linear regression test, t-test, f-test, determination test and sobel test. The result showed that has positive and website quality, flash sale, hedonic shopping motives significant influence towards the purchase impulsive. While positive emotion as the intervening variable has positive and significant influence towards the purchase impulsive. Keywords: website quality, sales promotion, hedonic shopping motives, purchase impulsive, positive emotion.